Treatment of Renal Stones - Amir, Saeed (Journal of Postgraduate Medical Institute, 2011)
to understand and update our knowledge about the evolution of renal stone treatment. A study of 50 consecutive cases of renal stones treated by open surgery in surgical unit AHQ Landikotal from january 2002 to December 2002 were included in the study. high success rate were achieved by open surgery int hose patients who presented earlier and had good renal functions. Open surgery still remains the choice of treatemnt espeically for large renal calculi in terms of stone clearance and stone free period.